ROLES OF ENGOS IN NITRATE CONFLICT MANAGEMENT: CASE STUDY: THE NETHERLANDS AND FLANDERS, BELGIUM - Linda Yanti Sulistiawati (Fakultas Hukum Universitas Gadjah Mada, 2008)
In developed countries, conflicts between environmental interests and agricultural emissions can not be avoided. Within the legal formal perspective, it is often assumed that all environmental conflicts are solved through the legal-formal system. In reality, however, the conflict between environmental concern and agricultural practices is complicated by wide variety of interests and mere legal formal approaches will not be adequate to solve them. This conflict as it relates to nitrate emissions will be referred to herein as the ‘nitrate conflict’. The role of civil society, in this case the Environmental Non-Governmental Organizations (ENGOs), are often neglected in the nitrate conflict management. This study will document and analyze nitrate con.ict management in the Netherlands and Flanders Belgium, on the roles of ENGOs regarding the issue. Moreover, the research will emphasize the important role of ENGOs in civic engagement in developing democratic and just environmental management.